The Implementation of Gottlieb’s Subtitling Strategies in the Film When Harry Met Sally - Ariza Purnawati; Ayesha Sofiah Karimah (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the subtitling strategies used in the translation of the film subtitle When Harry Met Sally from English to Indonesian. This study employs Henrik Gottlieb’s theory of subtitling strategies. A qualitative descriptive method is used, with data sources consisting of the English and Indonesian subtitles from the film. The data were analyzed based on the ten subtitling strategies proposed by Gottlieb: expansion, paraphrase, transfer, imitation, transcription, dislocation, condensation, decimation, deletion, and resignation. The results of the study indicate that paraphrase was the most dominant strategy, accounting for 36% of the total data. Conversely, dislocation and transcription were the least frequently used strategies, with each representing only 2%. The dominant use of the paraphrase strategy suggests that in films containing a significant amount of dialogue with ambiguity, metaphors, and figurative language, the paraphrase strategy is necessary to preserve meaning and prevent it from being lost in the translation process. Meanwhile, the dislocation strategy was rarely used because there were no singing scenes or significant musical elements in the film. Furthermore, the absence of a third language in the film’s dialogue meant that the transcription strategy was the least frequently used. These findings indicate that the choice of subtitling strategy is strongly influenced by the characteristics of the dialogue and the linguistic context of the film being translated.